Boundary Value Problems of Nonlinear Mixed-Type Fractional Differential Equations - Ping Yu; Hongju Li; Jian Ding; Yanli Ma (Journal of Mathematics)
In this paper, by means of a fixed point theorem for monotone decreasing operators on a cone, we discuss the existence of positive solutions for boundary value problems of nonlinear fractional singular differential equation. The proof of the main result is based on Gatica–Oliker–Waltman fixed-point theorem. At last, an example is given to illustrate our main conclusion.